A noninvasive tumor oxygenation imaging strategy using magnetic resonance imaging of endogenous blood and tissue water. Issue 2 (27th February 2013) - Zhang, Zhongwei; Hallac, Rami R.; Peschke, Peter; Mason, Ralph P.
<x xml:space="preserve">Abstract</x> Purpose To present a novel imaging strategy for noninvasive measurement of tumor oxygenation using MR imaging of endogenous blood and tissue water. Theory and Methods The proposed approach for oxygen partial pressure (pO2) estimation is based on intravoxel incoherent motion diffusion MRI and the dependence of the blood R2 relaxation rate on the inter‐echo spacing measured using a multiple spin‐echo Carr‐Purcell‐Meiboom‐Gill sequence and weak‐field diffusion model. The accuracy of the approach was validated by comparison with 19F MRI oximetry. Results The results in eight rats at 4.7 T showed that tumors have longer T1 (1980 ± 186 ms) and T2 (59 ± 9 ms) relaxation times, heterogeneous blood volume fraction (0.23 ± 0.1), oxygen saturation level (Y) (0.53 ± 0.12), and pO2 (36 ± 15 mmHg) distributions compared with normal muscle (T1 1480 ± 86 ms, T2 29 ± 2 ms, blood volume fraction 0.22 ± 0.03, Y 0.49 ± 0.06, and pO2 39 ± 5 mmHg). pO2 estimates based on the novel 1H approach were essentially identical with 19F observations. Conclusion The study indicates that noninvasive measurement of tumor pO2 using 1H MRI derived multiparametric maps is feasible and could become a valuable tool to evaluate tumor hypoxia. Magn Reson Med 71:561–569, 2014. © 2013 Wiley Periodicals, Inc.